META ANALISIS PENGARUH TEKANAN PENANGKAPAN TERHADAP UKURAN RAJUNGAN (Portunus pelagicus) DI TELUK BANTEN - Adi Susanto; Ririn Irnawati; Mustahal; Hery Sutrawan Nurdin; Yeni Marliana; Anggi Kurniasih; Niken Widowati; Tya Rizki Murniasih; Nuriman Affandi (Bogor Agricultural University, 2019)
Blue swimming crab (Portunus pelagicus) is an important economical fishery commodity for fishermen in Banten Bay that are caught using gill nets and collapsible traps. The increasing of fishing pressure has highly potential to reduce the quality of the catch as exposed in previous studies. However, the comprehensive, and time series analysis of the previous research results have not been conducted. The purpose of this study is to analyze the variations of blue swimming crab caught in Banten Bay through a combination of meta-analysis techniques, fishing trials and field obser-vations to determine the effect of fishing activities on swimming crab sizes, and evaluate the status of swimming crab fisheries in Banten Bay. Standard mean difference from 10 different studies was used as a meta-analysis parameter. The results of the meta-analysis showed that fishing activities were conducted from 2004 to 2018 had a significant effect on the decreasing of the swimming crab size. The average of swimming crab carapace width caught in 2019 approximately 121.66 mm. The proportion of legal swimming crabs in 2014, 2015 and 2019 was more than 80%, so that the status of swimming crab fisheries in Banten Bay is still environmentally friendly.Keywords: carapace width, meta analysis, fisheries, Portunus pelagicus, blue swimming crab